Video-Based Reflection and Peer Coaching in Enhancing TEFL Student-Teachers' Teaching Practices of Receptive Skills - Shaaban, Sumer Salman Abou (Journal of Education and e-Learning Research, 2022)
This study examines the effect of selfie video reflection, model lesson video reflection, and peer-coaching relating to model lesson videos and selfie videos on TEFL student-teachers' receptive skills teaching practices. An observation checklist of (11) teaching practices was used by the participants during reflection. Four groups of (6) participants carried out two practice teaching days each week for three months and met with the researcher monthly. The first group recorded their lessons and reflected on them. The second watched model lesson videos and reflected on the teacher's performance. The third watched videos of model lessons, reflecting on them with peers, as well as recording their practice teaching and reflecting on their performance with peers. The fourth received only educational supervisors' and mentor teachers' feedback. The results reveal that the use of peer coaching with the model lesson and self-recorded videos enhances teaching practices relating to receptive skills.